Discussant: 'Discriminating Data, a conversation with Wendy Hui Kyong Chun' - Pavoni, A. (Discriminating Data, a conversation with Wendy Hui Kyong Chun', 2022)
co-organised by CADA in partnership with the Lisbon Architecture Triennale and the Faculty of Fine Arts, University of Lisbon (Departments of Communication Design and of Multimedia Arts), as part of the public talks programme Human Entities 2022: culture in the age of artificial intelligence